Clinical practice guidelines for the treatment of invasive Aspergillus infections in adults in the Middle East region: Expert panel recommendations - Hail M. Al-Abdely; Adel F. Alothman; Jameela Al Salman; Tariq Al-Musawi; Muna Almaslamani; Adeel A. Butt; Abdulhakeem O. Al Thaqafi; Nirvana Raghubir; Waleed El Morsi; Nadine A. Yared (Elsevier, 2014)
Summary: The incidence of invasive Aspergillus infections in the Middle East continues to rise with the increase in the number of immunocompromised patients, and carries significant morbidity and mortality. A panel of experts analysed the evidence from the most recent international guidelines and relevant published literature to reach consensus and develop clear clinical practice guidelines to aid diagnosis and treatment of invasive Aspergillus infections in the Middle East. Disease-specific recommendations were provided for the management of invasive aspergillosis. The expert panel acknowledged that these guidelines should be followed as closely as possible but used alongside clinical judgement. Keywords: Aspergillus, Treatment, Guidelines, Aspergillosis, Middle East